Antimutagenic activity of compounds isolated from Ajuga bracteosa Wall ex. Benth against EMS induced mutagenicity in mice. (2018) - Ganaie, Hilal Ahmad; Ali, Md. Niamat; Ganai, Bashir A.; Bashir, Samirul
Graphical abstract: Schematic representation of compounds isolated from Ajuga bracteosa and their antimutagenic activity. Highlights: Four compounds 1 ) 14, 15-dihydroajugapitin and 2 ) 8-o-acetylharpagide were isolated from Ajuga bracteosa . A quick and sensitive HPLC method was developed for qualitative and quantitative determination of three isolated marker compounds from Ajuga bracteosa . The isolated compounds possess antimutagenic activity thus could be a possible source for the drug discovery for cancer. Abstract: Ajuga bracteosa Wall ex. Benth. (Lamiaceae) has been reported to possess many biological activities including antibacterial, antifungal, antispasmodic and antioxidant activity but there is no report as such on its mutagenic and/or anti-mutagenic activity. The aim of the present study was to isolate compounds from the methanol extract of the aerial parts of Ajuga bracteosa and determine their anti-mutagenic activity against the mutagen, EMS in animal model mice. The study was undertaken in order to corroborate the traditional use of the plant Ajuga bracteosa. The compounds were isolated from the methanol extract of the aerial parts of Ajuga bracteosa using silica gel column chromatography. Structural elucidation of the isolated compounds was done using spectral data analysis and comparison with literature. High performance liquid chromatography (HPLC) was used for the qualitative and quantitative determination of the isolated compounds in the crude methanol extract. The isolated compounds and standard drug were evaluated in vivo for antimutagenic activity against EMS induced mutagenicity taking mice as model organism by micronucleus and chromosomal aberration tests. Four major compounds were identified as 1) 14, 15-dihydroajugapitin 2) β- Sitosterol 3) Stigmasterol and 4) 8-O-acetylharpagide. A quick and sensitive HPLC method was developed for qualitative and quantitative determination of three isolated marker compounds from Ajuga bracteosa . 14, 15-dihydroajugapitin reduced the micronuclei by 85.10%, followed by β- Sitosterol (72.3%) while as 8-O-acetylharpagide reduced the micronuclei by 46%. It is therefore evident from the present study that the plant contains rich source of anticancer and antimutagenic drugs.